Lysosomal Acid Lipase Deficiency: Report of Five Cases across the Age Spectrum - Marco Antonio Curiati; Sandra Obikawa Kyosen; Vanessa Gonçalves Pereira; Francy Reis da Silva Patrício; Ana Maria Martins (Case Reports in Pediatrics)
Lysosomal acid lipase (LAL) deficiency is an autosomal recessive lysosomal storage disorder caused by mutations in the LIPA gene that leads to premature organ damage and mortality. We present retrospective data from medical records of 5 Brazilian patients, showing the broad clinical spectrum of the disease.